Electrochemically co-reduced 3D GO-C60 nanoassembly as an efficient nanocatalyst for electrochemical detection of bisphenol S. (10th January 2016) - Zhu, Wenxin; Yue, Xiaoyue; Duan, Jinyuan; Zhang, Yuhuan; Zhang, Wentao; Yu, Shaoxuan; Wang, Yanru; Zhang, Daohong; Wang, Jianlong
Abstract: Bisphenol S, the most ideal alternative of bisphenol A, has been proved to be toxic towards human. However, up to now, there is no rapid detection method established to cater to the on-site determination of bisphenol S. Herein, we pioneered an electrochemically co-reduced graphene oxide-C60 nanoassembly based electrochemical platform to cover this shortage. This nanoassembly synthesized by simple grinding and electrochemical reduction shows excellent electrocatalytic activity towards bisphenol S, and the novel electroanalytical platform allows a sensitive determination of bisphenol S in the range of 1–100 μM with a detection limit of 0.5 μM. Moreover, this sensor was utilized to determine bisphenol S in milk, emerging good anti-interference ability and acceptable recovery.